Students’ Visual Representation of Lights and Visions - Yogi Kuncoro Adi; Ari Widodo; Wahyu Sopandi; Muslim (Postgraduate, University of Mataram, 2023)
Visual representations are used by scientists to communicate scientific conceptions and are used by teachers to teach science in the classroom. The 2013 Curriculum textbook reduces this visual representation. Meanwhile, visual representations will help students develop a comprehensive understanding of the concept. This case study research aims to reveal cases of misconceptions in the visual representation of students at an X elementary school. We used observations of fifty-nine fourth-grade elementary school students to find students with different cases of misconceptions. Eleven students were further identified using interviews and drawing tests. We analysed the data qualitatively based on the collection of these two types of data. We found misconceptions in the representation of luminous objects and how students draw visions of luminous objects and non-luminous objects. Research results showed that we found cases of misconceptions similar to the findings from previous studies. While light and vision are prerequisite concepts, a student's conception of vision is affected when he has a misconception about light. Content can be developed by paying attention to the various modes of representation, conceptual change, and learning progression in the future. The pattern of learning progression can be studied in more detail using the microgenetic method.